SQLE promotes osteosarcoma progression via activating TGFβ/SMAD signaling pathway - Qi Song; Lina He; Jing Feng (Molecular and Cellular Probes, 2024)
Background: The prognosis of advanced osteosarcoma (OS) has remained stagnant in last decades, requiring the identification of novel therapeutic targets. Recently, much attention was paid to the role of squalene epoxidase (SQLE), a rate-limiting enzyme in cholesterol metabolism, in the field of oncology, while the specific role of SQLE in OS has not been sufficiently elucidated. The present study aims to investigate the role of SQLE in the progression of OS and explore the potential mechanisms. Methods: The expression levels of SQLE in OS tissues and adjacent normal tissues were compared using bioinformatic methods and experiments. Kaplan-Meier survival analysis and univariate and multivariate Cox analysis were performed to detect the association of SQLE expression and patient’ prognosis. Stably cell lines with SQLE knockdown or overexpression were constructed by lentivirus infection. CCK-8, colony formation, scratch healing, and Transwell invasion assays were carried out to explore the effect of SQLE knockdown or overexpression on the proliferation, migration, and invasion of OS cells. Gene set enrichment analysis was conducted to reveal signaling pathways associated with SQLE expression. The effect of SQLE on TGFβ/SMAD signaling pathway were explored by Western blot assay. Results: Here, we found a notable rise of SQLE expression in OS tissues and cell lines. Survival analysis showed that individuals with high SQLE expression had a lower median overall survival time compared to those with low SQLE expression. Univariate and multivariate Cox regression analyses showed that SQLE might have the potency to serve as an independently prognostic biomarker in OS. Loss- and gain-of-function experiments indicated that silence of SQLE suppressed OS cell proliferation, migration, and invasion, while overexpression of SQLE exerted the opposite effects. Mechanistically, TGF-β signaling pathway was identified as the downstream pathway of SQLE through bioinformatic methods, and the results of Western blot assay showed that SQLE positively regulated the activity of TGFβ1/SMAD2/3 signaling in OS. Resue experiments demonstrated that SB431542, a small molecule that inhibits TGFβ/SMAD signaling, could partly reverse the promoting effects of SQLE on OS cell proliferation, migration, and invasion. Conclusion: Our results provided preliminary evidences that SQLE was a tumor-promoting factor and prognosis predictor in OS. SQLE promoted OS cell proliferation, migration, and invasion via activating TGFβ/SMAD signaling and targeting SQLE might be a potential strategy for the treatment of OS.